Ragam Kata Sapaan Kekerabatan Minangkabau di Keluarga Inti Berdasarkan Matrilineal pada Remaja Minang - Syifa Fadhilah Gusman; Fidela Arminda; Wulan Hafizah; Yana Tasya Noveri; Fauziyyah Wardah Tuljannah (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2021)
Minangkabau is a regional language where it is used as the main language by indigenous people in Minangkabau. In minangkabau language the word greeting many undergo changes, especially the word greeting used by teenagers. In addition, the word greeting that already exists is not used anymore by teenagers today. The purpose of the research to be carried out by researchers is, as follows, to find out and describe what are the variety of greeting words used by Minang teenagers to their matrilineal nuclear family, to find out whether the use of greeting words in Minangkabau language begins to fade in Minang teenagers, to find out if minang teenagers still want to apply minangkabau language words in everyday life. The study involved 101 participants, which has been in accordance with the criteria of minang people, namely aged 15-24 years who are male and female. This criterion is prepared to obtain information related to the use of various words of matrilineal kinship in Minangkabau. Researchers used the open-ended-quotionnaire method. The analysis techniques in this study consist of open coding and selective coding. The results of the study can be concluded that, adolescent minang in using the word Minangkabau greeting based on matrilineal kinship undergoes many changes at this time. In addition, most of the subjects studied want to apply the word Minangkabau greeting in everyday life and in the future.